2023
DOI: 10.1371/journal.pone.0292330
|View full text |Cite
|
Sign up to set email alerts
|

Left-dominance for resting-state temporal low-gamma power in children with impaired word-decoding and without comorbid ADHD

Oliver H. M. Lasnick,
Roeland Hancock,
Fumiko Hoeft

Abstract: One theory of the origins of reading disorders (i.e., dyslexia) is a language network which cannot effectively ‘entrain’ to speech, with cascading effects on the development of phonological skills. Low-gamma (low-γ, 30–45 Hz) neural activity, particularly in the left hemisphere, is thought to correspond to tracking at phonemic rates in speech. The main goals of the current study were to investigate temporal low-γ band-power during rest in a sample of children and adolescents with and without reading disorder (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 73 publications
0
0
0
Order By: Relevance
“…Insignificant relationship between resting gamma power and dyslexia was reported (Babiloni et al, 2012;Lasnick et al, 2023). When analyzing auditory steady-state responses, the dyslexic group had a lower gamma peak frequency, while no significant differences in gamma power were observed (Rufener and Zaehle, 2021).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Insignificant relationship between resting gamma power and dyslexia was reported (Babiloni et al, 2012;Lasnick et al, 2023). When analyzing auditory steady-state responses, the dyslexic group had a lower gamma peak frequency, while no significant differences in gamma power were observed (Rufener and Zaehle, 2021).…”
Section: Introductionmentioning
confidence: 96%
“…One study found decreased beta power in the dyslexic group (Spironelli et al, 2008), while the other increased beta power relative to the control group (Rippon and Brunswick, 2000). Insignificant relationship between resting gamma power and dyslexia was reported (Babiloni et al, 2012; Lasnick et al, 2023). When analyzing auditory steady-state responses, the dyslexic group had a lower gamma peak frequency, while no significant differences in gamma power were observed (Rufener and Zaehle, 2021).…”
Section: Introductionmentioning
confidence: 99%